VARK LEARNING STYLE PROFILE OF ADULT LEARNERS OF KRISHI VIGYAN KENDRA - A. MARY SWARNALATHA, N. SUNITHA, P. AMALA KUMARI and (The Journal of Research, PJTSAU, 2017)
Learning styles is a term used to refer to the methods of gathering, processing, interpreting, organizing and thinking about information. Individual learning style refers to style or learning methods used in the process of learning. There are various views on learning style concepts and definitions among researchers and each investigates and observes from various aspects such as psychological andenvironmental aspects. These learning styles’ concepts and definitions show that learning has a cognitive, affective and behavioralcharacteristics, based on seeing, interacting and responding to methods in learning.